Nonthermal Processing of Food - Barbosa-Cánovas, Gustavo (2010)
Conventional approaches to process foods have proven to offer very safe products but, in some cases, the quality of the final product is significantly lower to the original one. Nonthermal processing of foods has emerged as a viable alternative to those conventional processing by offering safe products of excellent quality and at very reasonable cost. These emerging technologies utilize nonthermal microbial stress factors as the main inactivation mechanism. In some cases, external sources of heat or self-generated heat are utilized to supplement the main inactivation mechanism. This combination becomes very relevant in the case of the sterilization of low-acid foods by pressure assisted thermal processing (PATP). This article presents some of the most relevant nonthermal technologies where some of them are already in use by the food industry and others will be adopted in the very near future. It is the case; these nonthermal technologies could be used in combination among themselves or with other preservation approaches seeking synergistic effects in order to have shorter processes and very good quality food products.